Camelid diet through microhistological and palynological analyses of feces and coprolites from Parque Nacional Perito Moreno, Patagonia, Argentina - Agliano, Florencia; Velázquez, Nadia Jimena; Martínez Tosto, Ana Cecilia; Camiolo, Ivana Silvia; Rindel, Diego Damian (Journal of Archaeological Science: Reports)
Several palynological and microhistological studies have demonstrated the potential of coprolites analyses for understanding paleodiets and paleoenvironmental reconstructions of species of archaeological interest, such as Lama guanicoe (guanaco). The guanaco was the main food resource for hunter-gatherers from Patagonia, and this predator–prey relationship probably influenced their geographical and seasonal distribution during the Holocene.The aim of this study was to identify the food items consumed by camelids inhabiting the Parque Nacional Perito Moreno, Argentina. This study was carried out through the analysis of plant remains and pollen in modern feces and coprolites. The samples were collected from the Alero Destacamento Guardaparque archaeological site. Although plant remains and pollen in the modern feces were well preserved, the coprolites showed signs of poor preservation and exhibited fungal spores in all samples. The food items detected in the modern feces were similar with remains from the middle and late Holocene coprolites. They coincide with the current vegetation of the grass-shrub steppe. Plant species identified in the coprolites included Armeria maritima, Clinopodium darwinii, Colobanthus lycopodioides, Perezia recurvata, Senecio cuneatus, and various species of Poaceae, including Bromus setifolius, Deschampsia antarctica, Festuca pallescens, Nassella tenuis, Pappostipa chrysophylla, P. speciosa, Poa ligularis, and Rytidosperma sp. These results provide information about the diet of L. guanicoe which inhabited the area near the Alero Destacamento Guardaparque site. In addition, new detailed information for the reconstruction of paleoenvironments during the middle and late Holocene in the PNPM was obtained, which is crucial for ecological niche reconstructions. Several palynological and microhistological studies have demonstrated the potential of coprolites analyses for understanding paleodiets and paleoenvironmental reconstructions of species of archaeological interest, such as Lama ...